2017
DOI: 10.1073/pnas.1703161114
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast myosin Myo2 is down-regulated in actin affinity by light chain phosphorylation

Abstract: Studies in fission yeast have provided the basis for the most advanced models of the dynamics of the cytokinetic contractile ring. Myo2, a class-II myosin, is the major source of tension in the contractile ring, but how Myo2 is anchored and regulated to produce force is poorly understood. To enable more detailed biochemical/biophysical studies, Myo2 was expressed in the baculovirus/9 insect cell system with its two native light chains, Rlc1 and Cdc4. Milligram yields of soluble, unphosphorylated Myo2 were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 63 publications
(93 reference statements)
10
38
0
3
Order By: Relevance
“…Control preparations of skeletal muscle myosin contained bipolar filaments. These experiments are consistent with independent work by Pollard et al (), who found that Rlc1p phosphorylation does not affect the 7 S sedimentation coefficient or solubility of Myo2 in a range of KCl concentrations.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Control preparations of skeletal muscle myosin contained bipolar filaments. These experiments are consistent with independent work by Pollard et al (), who found that Rlc1p phosphorylation does not affect the 7 S sedimentation coefficient or solubility of Myo2 in a range of KCl concentrations.…”
Section: Resultssupporting
confidence: 92%
“…Transmission electron micrographs of these specimens contain only single molecules with two heads and a tail (Figure a and b). Pollard et al (Pollard et al, ) published similar micrographs of a few Myo2 molecules under unspecified conditions. The lengths of the Myo2 tails in our specimens varied from about 40 nm to more than 100 nm (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Related in vitro measurements in fission yeast were performed in ref. (Pollard et al, 2017), where the ATpase rate of fission yeast myosin Myo2 was measured versus actin concentration at saturating ATP levels.…”
Section: Dependence Of Fission Yeast Myosin-ii Activity On Atp Concenmentioning
confidence: 99%